2021
DOI: 10.3390/su13169265
|View full text |Cite
|
Sign up to set email alerts
|

Public’s Intention and Influencing Factors of Dockless Bike-Sharing in Central Urban Areas: A Case Study of Lanzhou City, China

Abstract: Taking the main district in Lanzhou city of China as an example, the questionnaires were designed and distributed, and then the effects of five factors, i.e., behavioral attitude, subjective norm, perceived behavioral control, perceived ease of use and perceived usefulness, on the behavioral intention of dockless bike-sharing (DBS) use were empirically analyzed based on the integrated model of technology acceptance model (TAM) and the theory of planned behavior (TPB) as well as the structural equation model. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Perceived value is the crucial factor influencing bike-sharing users’ payment intention with the highest influence value of 0.365, and the conclusion is consistent with some studies on China’s bike-sharing programs such as Ma et al (2018 , 2019) , and Ji et al (2021) . This means bike-sharing users put the utility gained from bike-sharing services first.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Perceived value is the crucial factor influencing bike-sharing users’ payment intention with the highest influence value of 0.365, and the conclusion is consistent with some studies on China’s bike-sharing programs such as Ma et al (2018 , 2019) , and Ji et al (2021) . This means bike-sharing users put the utility gained from bike-sharing services first.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
“…People whose illegal behaviors are recorded in the individual credit system will lose some credit scores. And they will not be able to enjoy bike-sharing services if their credit scores are lower than a certain degree, which can reduce bike-sharing uses’ illegal behaviors on shared bikes ( Ji et al, 2021 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Lanzhou, the capital city of Gansu Province, is located at the geometric center of China's map. It is not only an important center city, industrial base, and comprehensive transportation hub in the northwest region of China, but also a vital node along the Silk Road Economic Belt 22 . Due to its distinctive terrain and topography, the Yellow River flows from west to east through the city.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…It is believed that usefulness ease of use are key factors that influence users' attitudes and intentions to adopt new technologies. Mao et al, [14] are taken from previous study employed TAM in their studies to investigate potential buyers' attitudes towards VR technology in real estate marketing. They found that perceived usefulness and perceived ease of use were positively correlated with the intention to use VR technology.…”
Section: Vr 311 Definitionmentioning
confidence: 99%